Aspects of applying the method of chemical mutagenesis to develop cultivars of Calendula officinalis L. - F. M. Khazieva; I. N. Korotkikh (Труды по прикладной ботанике, генетике и селекции)
Background. The need for continuous breeding practice to develop new varieties of Calendula officinalis L. is induced by the accumulation of low-grade morphotypes in the already existing cultivars as a result of crosspollination. Materials and methods. Seeds selected from high-yielding biotypes of cv. ‘Kalta’ were treated with various mutagens for 18 hours, using 1000 seeds for each option. The mutation rate in the M1 generation and seed quality were determined, and plant viability was assessed under field conditions. Plant height, number of branches, number of leaves, number of inflorescences per plant, inflorescence diameter, number of ray floret rows, and weight of one inflorescence were measured in the mass flowering phase. The yield of raw materials (fresh and air-dry biomass of inflorescences) was calculated for each harvest and for the total amount of all 7 harvests during the flowering period. Results. The mutagens DES0,05% and DMS0,08% turned out the most effective for developing new source material. None of the plants produced seeds after treatment with nitrosomethyl urea (NMU0.02% ), and only one plant produced seeds after treatment with NMU0.04% . As a result of a long-term breeding process (2009–2016), new varieties were developed on the basis of mutant generations M2–M3 : cvs. ‘Zolotoe more’ and ‘Rajskij sad’, both exceeding cv. ‘Kalta’ in the yield of inflorescences by 39 and 30%, seed yield by 48 and 49%, total extractives by 13.8 and 21.3%, and total flavonoids by 29.9% and 43.3%, respectively. Conclusion. New cultivars of C. officinalis, ‘Zolotoe more’ and ‘Rajskij sad’, were developed in accordance with the mutation breeding scheme that employed methods of chemical mutagenesis, with expanded selection of plants altered in their morphological characteristics, productivity and content of bioactive compounds in the first mutant generation and assessment of uniformity, distinctness and stability in the second and subsequent generations.